Hubungan antara Self - Esteem dengan Fear of Missing Out (FOMO) pada Gen Z di Jawa Timur - Tri Kurniawati; Andhita Dyorita Khoiryasdien (EduInovasi: Journal of Basic Educational Studies, 2025)
This research aims to find out whether there is a relationship between Self Esteem and Fear of Missing Out (FoMO) in Gen Z in East Java. Fear of Missing Out (FoMO) is an individual's feeling when they feel afraid and worried about being left behind. FoMO is a very close relationship with psychological health and well-being. The FoMO phenomenon can affect anyone, especially Gen Z where this age is the age of searching for identity and all their activities are directly connected to social media. This study uses a descriptive and inferential quantitative approach with a simple regression analysis method. The subjects of this study were Gen Z in East Java aged 18-27 years who use social media with a sample of 120 people. Data were collected through an online survey via Google Forms that measured Self Esteem and Fear of Missing Out (FoMO) and distributed through social media. Data were analyzed using classical assumption tests and hypothesis tests in the form of simple regression analysis. the results of the study showed that there was a very significant influence between Self Esteem and Fear of Missing Out in Gen Z. This is indicated by the regression coefficient value of 459,000, which indicates that the higher the Self Esteem, the lower the FoMO so that Gen Z in East Java feels valuable and confident. this study still has shortcomings such as subjects that are not balanced between genders, not focusing on one social media, and research subjects that are still limited, therefore it is hoped that further research can improve the findings.